Morphological and Molecular Characterization of Potential Harmful Diatom, Pseudo-nitzschia from Sarawak Water with Description of a New Morphtype - Afiqah, Bt Hamilton Hanifah (Universiti Malaysia Sarawak (UNIMAS), 2017)
Pseudo-nazchia may hung a harmful potential to both human and other aquatic inhabitants. Despite having extensive research done o n Pseudo-nlfzchia, there are only a few research done on Pseudo-nilzchia m Sa rawak waters. Hence, the main objeclives of this study are to determine and understand the morphological as well as molecular characterizati on of Pseudo-l1ifzchia in Sarllwak waters together. The samples for this research we re collected at Satang Salak, Samauang, KnchIng and Miri, Sarawak usmg 20 ,.lin plankton net and Van-Dom wa ter sampl er fo r wa ter sample collechon. The samples were cultu red to obtain monoclonal cultures for morphology and molecular characterization. Internal transcnpt spacer (ITS) region was amplified and sequenced. P. sp. I was consisted of lanceolate va lve and long tapering to the apices which differed from P. ptlngens. Max imum Pa rsilllOny (MP) and Neigbour-Joining (NJ) trees were reconstructed. The phylogenet ic tnferred the distinct relationship between P. sp. 1 and P. pungens by fom1ing sister clade. The fin ding in thiS study was proven by the high species diversity in coastal o f Sarawak.